1990
DOI: 10.1152/jappl.1990.68.5.2107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-acetylcysteine on diaphragm fatigue

Abstract: It has recently been postulated that diaphragm fatigue may be due, at least in part, to a form of low-grade injury to subcellular organelles. Moreover, several studies have shown that thiol-containing compounds can protect cardiac and striated skeletal muscle organelles from the deleterious effects of a number of physiological stresses. The purpose of the present study was to determine whether pretreatment with N-acetylcysteine (NAC), a thiol-containing compound, would attenuate the rate of development of diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
137
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(151 citation statements)
references
References 0 publications
13
137
0
1
Order By: Relevance
“…Under basal conditions, unfatigued skeletal muscle produces reactive oxygen species (12) and nitric oxide (NO) derivatives (13,14) that have been shown to modulate excitation-contraction coupling (12,13). Strenuous contractile activity increases reactive oxidant production (14 -17), which contributes to fatigue of both isolated muscle preparations (15,16,18,19) and human muscle in vivo (20). Redox modulation of the ryanodine-binding protein has been proposed as a common mechanism for these effects (21).…”
mentioning
confidence: 99%
“…Under basal conditions, unfatigued skeletal muscle produces reactive oxygen species (12) and nitric oxide (NO) derivatives (13,14) that have been shown to modulate excitation-contraction coupling (12,13). Strenuous contractile activity increases reactive oxidant production (14 -17), which contributes to fatigue of both isolated muscle preparations (15,16,18,19) and human muscle in vivo (20). Redox modulation of the ryanodine-binding protein has been proposed as a common mechanism for these effects (21).…”
mentioning
confidence: 99%
“…Also, it was demonstrated that vitamin E could delay the onset of muscular fatigue [35]. Additionally N-acetylcysteine (NAC), which is also a very well recognized antioxidant, was also reported to prevent muscle fatigue in some experimental muscle preparations [36]. However, most of the studies regarding the positive effects of the antioxidants in this area of research are controversial, since some authors showed for example that both vitamin C and E did not affect in any way the performance of the exercise [4,37].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies feeding NAC to rats (1g/kg/day) showed similar decreases in blood GSH oxidation following exhaustive exercise (71). Shindoh et al, (80) observed an increase in muscular performance with NAC supplementation in rabbit diaphragm muscle. Rabbits were treated with either intravenous NAC or saline.…”
Section: Ros Generation and Fatiguementioning
confidence: 97%
“…However, one antioxidant, N-acetylcysteine (NAC), a known GSH booster, has improved performance in both animal and human models (see Table 1) (66,80). Indeed, direct GSH supplementation is ineffective in raising GSH because of its lipophobic properties and inability to cross cellular membranes (89).…”
Section: Ros Generation and Fatiguementioning
confidence: 99%